2019
DOI: 10.1136/bmjresp-2019-000469
|View full text |Cite
|
Sign up to set email alerts
|

Identifying causation in hypersensitivity pneumonitis: a British perspective

Abstract: BackgroundEstablishing whether patients are exposed to a ‘known cause’ is a key element in both the diagnostic assessment and the subsequent management of hypersensitivity pneumonitis (HP).ObjectiveThis study surveyed British interstitial lung disease (ILD) specialists to document current practice and opinion in relation to establishing causation in HP.MethodsBritish ILD consultants (pulmonologists) were invited by email to take part in a structured questionnaire survey, to provide estimates of demographic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…mould or birds), without distinguishing by source (occupational versus household). A recent series of 206 HP cases from the British Midlands is an exception [28]. It distinguishes, as we did also, mould-and avian-attributed diseases that are from occupational versus other sources (mould, 7 of 16 (44%); avian 4 of 37 (11%)).…”
Section: Discussionsupporting
confidence: 49%
“…mould or birds), without distinguishing by source (occupational versus household). A recent series of 206 HP cases from the British Midlands is an exception [28]. It distinguishes, as we did also, mould-and avian-attributed diseases that are from occupational versus other sources (mould, 7 of 16 (44%); avian 4 of 37 (11%)).…”
Section: Discussionsupporting
confidence: 49%
“…Only 50% of MDD-diagnosed cases in another study of 251 initially undifferentiated ILD had diagnostic confidence >50% for f-HP using a similar algorithmic approach, mostly due to the absence or incompleteness of clinical or radiologic findings despite all patients having undergone histopathologic confirmation [ 81 ]. Barber et al reported a survey of British clinicians who described only 32% of their suspected HP cases had identifiable causative antigens, with 40% undergoing BAL and 10% undergoing surgical biopsy [ 82 ].…”
Section: Diagnosis: Where the Whole Is Greater Than The Sum Of Its Partsmentioning
confidence: 99%
“…Varied use and clinical value attributed to certain diagnostic elements may bias decision-making in both algorithmic and MDD approaches [ 82 , 83 ]. For example, a plausible exposure history (pet bird owner) and typical radiologic findings may lead to a confident diagnosis without additional invasive testing, while initially unclassifiable ILD may still have a broad differential diagnosis that only tentatively includes f-HP if exposure history is dubious, a UIP-like CT pattern is encountered, and histopathology is only suggestive but not definitive for HP.…”
Section: Diagnosis: Where the Whole Is Greater Than The Sum Of Its Partsmentioning
confidence: 99%
“…Interstitial lung diseases are a broad spectrum of lung pathologies that can be divided into two groups: ILDs with a known cause and ILDs without a known cause that give rise to the idiopathic form of pulmonary fibrosis [2,3]. Furthermore, the possible causes of the ILDs identified are represented by systemic diseases such as connective tissue disease [4,5] or environmental exposure to pneumotoxic drugs [6], radiation therapy [6], occupational exposures (e.g., asbestosis) [7] or allergens in the case of hypersensitivity pneumonitis [8]. The discrimination among different ILDs that present hetherogeneous inflammatory and fibrotic patterns even among patients with the same disease is critical for a more predictable prognosis and a more efficient management of the patients.…”
Section: Introductionmentioning
confidence: 99%